Cushing Syndrome Secondary to Primary Neuroendocrine Lung Carcinoma - A. Zainal; O. Akinsola; K. Rajamani (Case Reports in Endocrinology, 2019)
Cushing syndrome (CS) is a disorder characterized by a result of chronic exposure to excessive glucocorticoids. This article describes a case of a 30-year-old female presenting with fatigue, abdominal striae, unintentional weight gain, and lipodystrophy. A rare diagnosis of ectopic adrenocorticotropic-dependent CS was determined and a neuroendocrine lung tumor (NET) was discovered on chest x-ray. After surgical resection, pathology confirmed lung NET that stained positive for adrenocorticotropic hormone (ACTH). The patient’s symptoms fully resolved. The authors aim to urge clinicians to maintain a high index of suspicion for ectopic ACTH secretion (EAS) through a multimodal approach when caring for patients with CS.